2021
DOI: 10.17853/1994-5639-2021-1-44-72
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z and student volunteering: A national culture perspective

Abstract: Introduction. Volunteering in the modern world is one of the basic resources for solving society’s problems, an activity that helps students in different countries to build personal and professional competencies. The limited research that makes it possible to analyse the cross-cultural elements of student volunteering has led to a scientific interest in the problem of matching the cultural context and volunteer activities of students from universities in India, Russia and Croatia. The new research perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Mindfulness enhances student ability to focus on one task at a time, preventing distractions from simultaneously thinking about multiple tasks they need to accomplish [31]. It involves accepting new ideas, as individuals often form opinions based on initial impressions and stick to them even when contradictory evidence arises [32][33][34]. Being open to accepting new ideas often comes from multiple sources that mentally stimulate individuals [35,36].…”
Section: Mindfulnessmentioning
confidence: 99%
“…Mindfulness enhances student ability to focus on one task at a time, preventing distractions from simultaneously thinking about multiple tasks they need to accomplish [31]. It involves accepting new ideas, as individuals often form opinions based on initial impressions and stick to them even when contradictory evidence arises [32][33][34]. Being open to accepting new ideas often comes from multiple sources that mentally stimulate individuals [35,36].…”
Section: Mindfulnessmentioning
confidence: 99%
“…Global studies on the relationship between volunteerism and the millennial generation have indicated that social events, opportunities to uphold values and principles and the use of information technologies improve their awareness of inequalities, injustices and societal issues that need interventions (Adha et al 2018). Moreover, as a digital-first generation, they see no limits to communication, sharing information and volunteering-leaving a trace encouraging others to volunteer and recruit people (Perić et al 2021).…”
Section: Volunteering In a Crisismentioning
confidence: 99%
“…13 Research conducted in China, as well as internationally, indicates that limited public engagement in volunteer services often stems from insufficient policy guidance and low participant motivation. 14,15 Additionally, the lack of platform support and strategic direction for elderly voluntary services contributes to these challenges. 16,17 As a result, volunteers frequently encounter difficulties, grappling with how to effectively start and make a meaningful impact.…”
mentioning
confidence: 99%